2020
DOI: 10.1002/rmv.2198
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles of long non‐coding RNAs in viral diseases

Abstract: Summary Viral infection leads to large alterations in the host transcriptome and stimulates an antiviral host immune response involving numerous proteins and signalling pathways. Long non‐coding RNAs (lncRNAs) have emerged as important regulators during viral infection. Emerging data demonstrates that lncRNAs play essential roles at the host pathogen interface modulating viral infection by either antiviral response at distinct level including pathogen recognition receptors or by epigenetic, transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 128 publications
(202 reference statements)
1
20
0
Order By: Relevance
“…Evidence indicates that lncRNAs act as versatile molecules in regulating various biological processes, such as differentiation, apoptosis, and immune responses [ 11–13 ]. lncRNAs regulate gene expression by regulating transcriptional factors, inducing chromatin modification, affecting RNA processing events, sponging microRNAs (miRNAs), and affecting RNA stability [ 14 ]. While a substantially large number of studies have investigated lncRNAs in various types of cancers as therapeutic vulnerabilities and prognostic markers, the role that lncRNAs play to regulate innate as well as acquired immune processes has not been extensively studied in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that lncRNAs act as versatile molecules in regulating various biological processes, such as differentiation, apoptosis, and immune responses [ 11–13 ]. lncRNAs regulate gene expression by regulating transcriptional factors, inducing chromatin modification, affecting RNA processing events, sponging microRNAs (miRNAs), and affecting RNA stability [ 14 ]. While a substantially large number of studies have investigated lncRNAs in various types of cancers as therapeutic vulnerabilities and prognostic markers, the role that lncRNAs play to regulate innate as well as acquired immune processes has not been extensively studied in animals.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs play crucial roles in the host response to viral infections (Ginn et al;Kesheh et al;Fortes and Morris 2016;Liu and Ding 2017). However, previous studies mostly focused on specific cell lines or bulk tissues.…”
Section: Cell-type Dynamic Regulation Of Lncrnas Upon Ebov Infectionmentioning
confidence: 99%
“…In vitro and in vivo models showed that after IAV infection especially in lung cells, according to corresponding retinoic acid‐inducible gene I (RIG‐I)‐dependent signalling pathway and following interferon beta (IFN‐β) induction, the level of interferon‐stimulated lncRNA (lncRNA ISR) increased and it was able to suppress viral replication. 31 , 32 …”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…In vitro and in vivo models showed that after IAV infection especially in lung cells, according to corresponding retinoic acid-inducible gene I (RIG-I)-dependent signalling pathway and following interferon beta (IFN-β) induction, the level of interferon-stimulated lncRNA (lncRNA ISR) increased and it was able to suppress viral replication. 31,32 ISG20 belongs to the 3 0 -5 0 exonuclease super family that displays effective antiviral activity against several RNA viruses, including IAV. ISG20 inhibits the replication of IAV by interacting with viral NP protein and inhibiting viral polymerase activity.…”
Section: Lncrnas That Prevent Iav Replicationmentioning
confidence: 99%